Persepsi Siswa SMP Muhammadiyah Boarding School Yogyakarta Terhadap Pembelajaran Bahasa Arab - Linawati, Sri Lestari (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2022)
This study aims to, first, determine the perception of students of SMP Muhammadiyah Boarding School (MBS) Yogyakarta of the Arabic language, in terms of two aspects: the level of ease of Arabic and its main function. Second, to determine whether the factors educational background, family background and learning methods can explain students' perceptions about Arabic learning. With the research subjects were students in grade 3 (last class) of SMP MBS Yogyakarta. This study used mixed methods (method mix) with concurrent triangulation strategy, to collect quantitative and qualitative data concurrently, at a time. Furthermore, the two databases were compared to determine whether there is convergence , the differences, or some combination. In this way, mixing occurs when the researchers came to the stage of interpretation and discussion. Analysis of the data showed that the perception of students of SMP MBS Yogyakarta on the level of ease of Arabic language, the majority (65.62 %) stated